What are Churches For? Toward an Ecclesiology of the Cross after Christendom - Mahn, Jason A. (Dialog, 2012)
This essay applies pressure to Douglas John Hall's use of Luther's theologia crucis in his calls for the church to become an ecclesia crucis. In my analysis, the theology of the cross is best used not as a hermeneutical key for discerning Christendom's end and the church's new beginning, but as training in developing the capacity to discern both God and church as they hide under opposite signs. By drawing on Hall, two feminist Lutheran theologians, and Stanley Hauerwas, the essay suggests that the practices of the institutional church might be exactly what is needed for the formation of theologians of the cross.